How rationality predicts individual perception of safety climate: An application of the hybrid model of learning in personality - Mustika, Martina Dwi; Jackson, Chris J. (Psikohumaniora: Jurnal Penelitian Psikologi, 2020)
Jackson’s Hybrid Model of Learning in Personality (HMLP) is designed to measure the effect of biological, socio-cognitive, and experiential processes of personality and learning mechanisms on developing rationality and directing functional or dysfunctional behaviors of employees. We use HMLP to determine if rational thinking predicts individual perception of safety climate. The results found that the proposed indirect paths of learning mechanisms significantly predict the individual perception of a safety climate through rationality. The goodness-of-fit demonstrated that the model provided a satisfactory fit: c2 = 13.200, p = .067; RMS = .000; RMSEA = .063; GFI = .981; AGFI = .943; and CFI = .988. As a result, we identify the importance of rationality in predicting individual safety climate and once again confirm the usefulness of HMLP in predicting useful workplace outcomes. The HMLP offers valuable insights into the influence of rationality in predicting individual perception of safety climate, as well as the underlying process of developing rationality.